Impact of Balanced Fertilization on Carbon and Nutrient Dynamics under Long-Term Jute-Rice-Lentil Cropping System in Alluvial Soils of Eastern India. Issue 13 (20th July 2022) - Mazumdar, Sonali Paul; Saha, Amit Ranjan; Majumdar, Bijan; Kumar, Mukesh; Alam, Nurnabi Meherul; Saha, Ritesh; Dey, Pradip; Kar, Gouranga
ABSTRACT: A long-term experiment was conducted for 8 years to assess the impact of imbalance and balance fertilization based on soil test-based nutrient management practices on different carbon fractions, carbon (C) stocks, sequestration, C indexes and soil quality under Jute-rice-lentil cropping system in subtropical India. The 10 treatments were laid out in a randomized block design. Treatments included the use of farm yard manure (FYM), bio-inoculants and inorganic fertilizers at different rates and combinations. Results revealed that conjunctive use of inorganic fertilizer based on soil test and targeted yield approach, organic manure (FYM) and bio-inoculants was found to be superior in comparison to other nutrient management practices in terms of sustaining crop productivity and enhancing soil quality. Integrated soil test-based nutrient management increased total soil organic carbon (TSOC) by 16.9% compared to initial values and permanganate oxidizable C (KMnO4 -C) to the extent of 26.2% over the control. Soil microbial biomass carbon (SMBC) (374 μg g −1 soil) and microbial quotient (3.3%) were also found highest in integrated soil test-based nutrient management treatment. SMBC and KMnO4 -C constituted to the TSOC to the extent of 1.7 to 3.34% and 12.6 to 13.8%. The highest carbon management index value (129) was obtained in the treatment with integrated application of balanced fertilizes based on soil test and targeted yield, indicating that this system has better soil quality than the other management systems. C sequestration rate in the study varied from 0.015 to 0.16 Mg C ha −1 yr −1 under different treatments.